The brave little puppy and other stories - Blyton, Enid (Award Worksop, 1993)
The Brave Little Puppy and Other Stories is a delightful children's book featuring a collection of heartwarming tales about a courageous puppy and his friends. Each story revolves around themes of bravery, friendship, and adventure, with the puppy often leading the way in overcoming challenges and learning valuable life lessons. The engaging stories are complemented by vivid illustrations, making it a captivating read for young children.